IoT-Based Ship Tank Leak Detection System Prototype to Enhance Security - Mutawakil, Naufal Hanif; Yusfrizal; Ratih Puspadini, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This research discusses the design and development of a Prototype Ship Tank Leak Detection System Based on the Internet of Things (IoT) to enhance safety and operational efficiency of ships. This system utilizes the ESP32 microcontroller connected to an ultrasonic sensor to detect changes in liquid volume within the tank. The detection results are displayed via an LCD and sent in real-time to the Blynk application on smartphones, accompanied by an alarm in the form of a buzzer as an early warning. The implementation results show that the system is capable of detecting leaks effectively and provides notifications quickly when there is a significant decrease in liquid volume.